2019
DOI: 10.1111/1460-6984.12453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of effortful swallowing training on tongue strength and oropharyngeal swallowing function in stroke patients with dysphagia: a double‐blind, randomized controlled trial

Abstract: Background Effortful swallowing training (EST) is a remedial method for the training of swallowing‐related muscles in the oropharyngeal phase. However, clinical evidence of its effectiveness is insufficient. Aims To investigate the effects of EST on tongue strength and swallowing function in patients with stroke. Methods & Procedures Stroke patients with dysphagia were randomly assigned to one of two groups: an experimental group (n = 12) and a control group (n = 12). The experimental group underwent EST, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 13 publications
2
53
0
13
Order By: Relevance
“…In an RCT in which healthy subjects were treated with either effortful swallowing or a sham exercise, a non-significant increase in tongue strength was found in the treatment group after 4 weeks of intervention [ 192 ]. In a small RCT, in which dysphagic stroke patients either used effortful swallowing or performed a sham exercise (saliva swallowing), the intervention was associated with a significant improvement in tongue strength and oral swallowing function [ 193 ]. In addition, a small cohort study of Parkinson patients showed an increase in manometric pharyngeal pressure levels [ 194 ].…”
Section: Therapymentioning
confidence: 99%
“…In an RCT in which healthy subjects were treated with either effortful swallowing or a sham exercise, a non-significant increase in tongue strength was found in the treatment group after 4 weeks of intervention [ 192 ]. In a small RCT, in which dysphagic stroke patients either used effortful swallowing or performed a sham exercise (saliva swallowing), the intervention was associated with a significant improvement in tongue strength and oral swallowing function [ 193 ]. In addition, a small cohort study of Parkinson patients showed an increase in manometric pharyngeal pressure levels [ 194 ].…”
Section: Therapymentioning
confidence: 99%
“…First, the current study implemented effortful prolonged swallowing, a combination of effortful swallowing training and the Mendelsohn maneuver training. In previous studies, training outcomes of effortful swallowing alone only revealed significant increases in the maximum isometric pressure of the anterior tongue, lingua-palatal pressures, and swallowing functions [ 41 , 45 ]. However, in this study, effortful prolonged swallowing positively affected swallowing tongue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported this outcome [38,[40][41][42], using the Functional Dysphagia Scale (FDS) [67]; Videofluoroscopy Scoring Scale (VFSS) [68] and Videofluoroscopic Dysphagia Scale [69]. Meta-analysis of three studies reporting continuous outcomes found a beneficial effect from swallowing therapy (n = 64, SMD (FDS, VFSS, VDS scores) − 0.78, 95% CI − 1.3 to − 0.26, I 2 = 39%, P = 0.003) (very low certainty).…”
Section: Change In Pharyngeal Residue Severitymentioning
confidence: 96%
“…All studies reported rationale for treatment, materials and procedures used and the number, frequency, timing and intensity of treatment sessions. Thirteen studies reported who delivered the intervention [28, 29, 32-34, 37-39, 41, 42, 45, 47, 48] and seven detailed the training and/or experience of such personnel [27,29,33,39,41,42,45]. Thirteen studies provided information on whether treatments were tailored [27, 28, 30, 31, 33, 35, 37-40, 43, 45, 48], and no studies reported if an intervention was modified or whether intervention adherence assessment was completed.…”
Section: Intervention Reporting and Replicationmentioning
confidence: 99%
See 1 more Smart Citation